The effects of Porphyromonas gingivalis on the cell cycle progression of human gingival epithelial cells. (28th February 2013) - Pan, C; Xu, X; Tan, L; Lin, L; Pan, Y
<x xml:space="preserve">Abstract</x> Objective Porphyromonas gingivalis is a major pathogen in the development and progression of periodontal disease. The interactions or cross‐talk between bacteria and gingival epithelial cells drive bacteria to manipulate the cell cycle to favor bacterial survival and virulence expression within the host. This study aims to dissect the effects of P. gingivalis on the cell cycle in human gingival epithelial cells. Materials and Methods We established a model of P. gingivalis invading IHGE cells. The cell cycle distribution of human gingival epithelial cells was analyzed by flow cytometry. Cyclin D and cyclin E mRNA and protein were detected by real‐time PCR and Western blot, respectively. Results Porphyromonas gingivalis‐induced facilitation of cell growth was correlated with the acceleration of G1 phase of cell cycle. Cyclin D1 mRNA levels were significantly upregulated from 6 to 12 h after infection. Cyclin E protein and mRNA levels were elevated at 10 and 12 h after invasion. Conclusions We confirmed that P. gingivalis significantly enhances IHGE cell proliferation by promoting the G1/S transition, involving the up‐regulation of cyclin D and cyclin E.